Palliative care services for advanced non-malignant lung diseases in Taiwan. Issue 1 (1st June 2011) - Chan, T T; Lin, M S; Yu, C J; Hsu, J Y; Wang, J D; Yan, Y H; Partridge, M; Chen, C R
Abstract : Although hospice services has been available for cancer patients for 20 years in Taiwan, that for non-malignant diseases was started only since September, 2009. How well clinicians in this country are prepared for this challenge is unknown. A questionnaire was completed by 149 mostly respiratory clinicians (including 41 physicians, 65 nurses, 36 respiratory therapists, ) in three large hospitals from northern, central and southern Taiwan. Although hospice inpatient, outpatient and home care services were provided by all 3 hospitals, only 24–35% of clinicians reported easy access of these services. Fifty percent of physicians had referred patients at risk of respiratory failure to palliative care team, and the main reasons of non-referral were resource factors and no request by patients. Only 8.1% of all respondents had explicit policies and procedures of end-of-life care for patients with non-malignant lung diseases in their hospitals. Such policies or procedures were thought to be developed by the hospice team in 8.1%, and by pulmonologist or intensivist in 6.7%. For COPD patients, majority of physicians suggested discussion of end-of-life issues when patients were in severe disease (GOLD stage III), less than 100 m in 6-min walking test, after 2 to 3 admissions or ER visits for acute exacerbations in the past year, or after 1 respiratory failure attack. Almost all of them considered current palliative care for non-malignant lung disease patients having a long way to go to meet their needs. Among others, professional recruitment and development, public education and medical practice guidelines were those most urgently expected.